Industrial training report: Pens Leisure And Services Sdn Bhd - Mazlan, Muhammad Shamiel Aiman (Universiti Teknologi MARA, Perlis, 2024)
This executive summary includes 6 months of transformative industry training completed at Pens Leisure And Services Sdn Bhd in the Marketing and Administration Department. Starting on March 13, 2024, and ending on August 21, 2024, this internship is an essential requirement for the culmination of my studies in Marketing for this semester. As a beginner in the professional world, every moment of this training provides immeasurable value an experience that cannot be fully captured by words. This accumulation of experience, however, has proven invaluable for my future career trajectory. Eager to apply the theoretical knowledge gained during my studies, I approached this opportunity with enthusiasm and a thirst for new insights. Pens Leisure And Services Sdn. Bhd. operate on a B2B basis that will involve employees communicating with customers face-to-face or online. The company is largely controlled by Puan NurSyuhada binti Abd Aziz who is the manager in the marketing and administration department. This experience gave me the opportunity to acquire new complementary knowledge and skills my daily responsibilities in the Administration and Marketing Department. This dual exposure not only broadened my understanding but also improved my ability to multitask effectively. While managing the business of promoting the services provided by the company, I was simultaneously involved in administrative and human resource related tasks. The report comprehensively describes the advantages of industrial training, emphasizing the knowledge and abilities gained in areas such as multitasking and problem solving. Most of the document is devoted to a comprehensive SWOT analysis of Pens Leisure And Services Sdn Bhd, complete with infographics and detailed explanations of each component. Strategic recommendations are also given to maintain strengths, minimize weaknesses, capitalize on opportunities and counter potential threats. Internships have proven to be very rewarding and fulfilling, providing insight into the various viewpoints and dynamics of the world of work. This report is testament to the important journey completed at Pens Leisure, and I look forward to using this experience in my future endeavours.